IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE PS2G2 DALAM MEMPERBAIKI KEJUJURAN PESERTA DIDIK DI SMAN 1 PETANG TAHUN 2017 - Dunia, I Made (Jurnal Santiaji Pendidikan (JSP), 2017)
Honesty is one of the nation's characters that must be grown for a civilized nation. But unfortunately honesty seems to have faded in various lines of life, especially in school. This study aims to describe the effect of the implementation of cooperative learning model type PS2G2 to the student’s understanding of honesty and student’s honest behavior. The study was conducted in two cycles. Each cycle consists of 4 stages of action planning, action implementation, observation and reflection. The understanding of honesty data was collected through a questionnaire with Likert scale (1-5) and the students 'honest behavior data was collected through questionnaire (Likert scale) (1-4) and also using observation sheet with scale 100. The data have been collected, and then analyzed descriptively to draw conclusions. The results of Implementation of PS2G2 method in students in the classroom are as follows: students' understanding of honest understanding up 11.1% (target 10%). The value of student’s honest behavior increased until 9.4% (target 5%). Thus it can be concluded that cooperative learning model of PS2G2 type can improve understanding about honest and honest behavior of student.